2013
DOI: 10.1017/erm.2013.2
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of mesenchymal stem cells to osteoblasts and chondrocytes: a focus on adenosine receptors

Abstract: Skeletogenesis, either during development, post-injury or for maintenance, is a carefully coordinated process reliant on the appropriate differentiation of mesenchymal stem cells. Some well described, as well as a new regulator of this process (adenosine receptors), are alike in that they signal via cyclic-AMP (cAMP). This review highlights the known contribution of cAMP signalling to mesenchymal stem cell differentiation to osteoblasts and to chondrocytes. Focus has been given to how these regulators influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 125 publications
0
31
0
1
Order By: Relevance
“…For further details, the authors refer the reader to a recently published review article in this field [5].…”
Section: Purinergic Signalling In Cpcs and Autocrine/paracrine Regulamentioning
confidence: 99%
“…For further details, the authors refer the reader to a recently published review article in this field [5].…”
Section: Purinergic Signalling In Cpcs and Autocrine/paracrine Regulamentioning
confidence: 99%
“…It should be noted that the same P1 receptor subtypes were found to be expressed in articular chondrocytes [87]. A 2A and A 2B adenosine receptors are of particular importance as these are coupled to G s , which stimulates AC and produces a cAMP signal [88]; cAMP mediated signalling is a well known mediator of chondrogenesis as well as in maintaining the chondrocyte phenotype [89].…”
Section: P1 Adenosine Receptor Expression and Function During Chondromentioning
confidence: 97%
“…Repair of the skeletal system depends on the differentiation of osteoblasts from their progenitors (mesenchymal stem cells, MSCs) which have a broad, multilineage differentiation potential and express A1, A2A, A2B, and A3 receptors [67,68] (see Fig. 3).…”
Section: Regulation Of Osteoblast Differentiation and Function By Adementioning
confidence: 99%
“…Adenosine promotes osteoblast differentiation primarily through the A2BR receptor [68,78,80]. Rao et al showed that A2B receptors may be integral in the maturation of bone tissue, as their expression increases as a function of time [81].…”
Section: P1 Receptors: A2brmentioning
confidence: 99%
See 1 more Smart Citation